ENHANCING TEACHER PRODUCTIVITY THROUGH INTEGRATED MANAGEMENT RESOURCES: A MIXED-METHODS STUDY IN INDONESIAN ISLAMIC ELEMENTARY SCHOOLS - Sudiyah Anawati; Sri Setyaningsih; Dian Wulandari (SUJANA: Education and Learning Review, 2025)
Teacher productivity remains a critical challenge in achieving educational quality, particularly in resource-constrained contexts. This study examined the direct and mediated effects of empowerment, knowledge sharing, job design, and academic supervision on teacher productivity in Indonesian Islamic Integrated Elementary Schools. A sequential explanatory mixed-methods design combined qualitative interviews with 12 school principals and teachers with quantitative surveys of 176 teachers across 10 schools in East Jakarta. Structural equation modeling revealed that academic supervision was the strongest predictor of teacher productivity (β=0.641, p<0.001), explaining 41% of productivity variance, while empowerment, knowledge sharing, and job design showed no significant direct effects. However, knowledge sharing strongly influenced job design (β=0.750, p<0.001) and academic supervision (β=0.749, p<0.001), with academic supervision fully mediating empowerment effects and partially mediating knowledge sharing effects on productivity. The integrated model explained 83.1% of productivity variance with strong predictive validity (Q²=0.823). SITOREM analysis identified follow-up, supervision discussion, knowledge donation, and teacher autonomy as priority improvement areas. Findings demonstrate that productivity enhancement requires quality academic supervision integrated with supportive organizational cultures rather than isolated interventions. The study provides evidence-based strategies for educational administrators in developing contexts where strategic resource allocation is essential for maximizing teacher performance and student outcomes.